2017
DOI: 10.1021/acsami.6b14803
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced Thermoelectric Properties of Bi/Bi2S3 Nanocomposites

Abstract: Bismuth sulfide (BiS) has been of high interest for thermoelectric applications due to the high abundance of sulfur on Earth. However, the low electrical conductivity of pristine BiS results in a low figure of merit (ZT). In this work, BiS@Bi core-shell nanowires with different Bi shell thicknesses were prepared by a hydrothermal method. The core-shell nanowires were densified to Bi/BiS nanocomposite by spark plasma sintering (SPS), and the structure of the nanowire was maintained as the nanocomposite due to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(63 citation statements)
references
References 30 publications
2
59
0
2
Order By: Relevance
“…Therefore, the zT s are usually high in tellurides and selenides, but they are low in sulfides. This is the general phenomenon that has been observed in those well‐known TE materials such as Bi 2 X 3 ‐, SnX‐, and PbX‐based compounds (X = S, Se, and Te) . As shown in Figure , the zT values gradually improve as the anion element change from S to Se and then to Te.…”
supporting
confidence: 52%
“…Therefore, the zT s are usually high in tellurides and selenides, but they are low in sulfides. This is the general phenomenon that has been observed in those well‐known TE materials such as Bi 2 X 3 ‐, SnX‐, and PbX‐based compounds (X = S, Se, and Te) . As shown in Figure , the zT values gradually improve as the anion element change from S to Se and then to Te.…”
supporting
confidence: 52%
“…Recently, Ge et al. reported that the composite of Bi/Bi 2 S 3 holds highly enhanced thermoelectric properties, indicating that increasing Bi‐level in their sulfide parent phase is an effective strategy to achieve high performance samples. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the application of bare Bi 2 S 3 is still limited as the recombination process of the photogenerated electron-hole pairs is fast. So many methods were developed to ameliorate the photocatalytic activity of Bi 2 S 3 including morphology control [17], vacancy introduction [18], combination of other semiconductors [19], fabrication of heterojunction [20], incorporation of conductive materials (graphene) [21] or surface plasma resonance [22], etc. Among them, the fabrication of the heterojunction structure was a facile and effective method to improve the photocatalytic properties of the photocatalysts.…”
Section: Introductionmentioning
confidence: 99%